DIVERSITY OF THE ENDOPHYTIC FUNGI ISOLATED FROM SPILANTHES ACMELLA LINN. - A PROMISING MEDICINAL PLANT - H. C. LAKSHMAN; JAYSHREE M. KURANDAWAD (International Journal of Pharma and Bio Sciences, 2013)
A total of 300 segments from 18 plants of Spilanthes acmella Linn., were collected from Karnatak University Botanical Garden Dharwad. And they were screened for the presence of endophytic fungi. Altogether 8 fungal species; viz Aspergillus flavipes Bainer & Sartory, Aspergillus niger Tiegh., Aureobasidium pullulans (De Bary.) Arnaud. & Les, Bipolaris nodulosa (Bert and Curt. ex. Sacc.) Shoemaker., Cladosporium epiphyllum Person., Colletrichum Cord., Hymenula affinis (Fautrey and Lambotte)., Rhizopus nodusus Namyslowski. they were isolated and identified based on the morphology of the spores. The main isolation of endophytes, scanned out their diversity in the host. The results revealed the growth of endophytes on media PDA media MEA medium, colonization frequency of endophytic fungi significantly highest in leaves and greater activity in host leaves have been documented.